CULTURAL CONCEPTS IN HISTORICAL PROJECT BY PREM TINSULANONDA NAKHON RATCHASIMA PROVINCE FOUNDATION - Paehsakul, Prajak; Wannajun, Sisikka (Journal of Buddhist Anthropology, 2021)
The objectives of this research article were to study the cultural concepts including cultural landscape, collective memory, identity concept, and cultural values from the historical project that was awarded from the Regional Student Project Contest organized by Prem Tinsulanonda Nakhon Ratchasima Province Foundation during 2014 - 2018 in 50 subjects. The study was analyzed by using documentary research and analyzing data from the text. Characteristics of the cultural concepts were studied such as cultural landscape, collective memory, concept of identity, and cultural values. The research was presented in the form of analytical description. The results of the study showed that cultural concepts are applied in the history project in accordance with the study of history and culture in foreign countries as follows: 1) cultural landscape were found in describing community settlements, the origin, name importance, beliefs about space, and changes in the area that affect the community 2) collective memory found from interviews of the informant that the past events affect the way of life and evoke proudness, 3) an identity concept found descriptions of the distinctive features and significance of the subjects studied, such as the way of life of people, wisdom, traditions, local archaeological sites. It is believed that it is a unique identity found only in one's own locality, and 4) the concept of cultural value found in the explanations of the cultural values of the project which are the identity value, the artistic value, and the rare numerical values which are belief, faith, unity, wisdom which was beneficially used for the benefit of the environment, disease treatment, occupation and fine arts which are the social heritage of local people. Therefore, joint studies of cultural and historical concepts should be promoted.